Supervising third-party control bodies for certification: The case of organic farming in Italy - Annalisa Zezza; Federica De Maria; Tiziana Laureti; Luca Secondi (Agricultural and Food Economics, 2020)
The organic food certification system in Italy, based on the EU legislation, relies on private control bodies (CBs) that are supervised by national authorities. The aim of this paper is to investigate whether it is possible to test for differences in controls outcome based on CBs' behavior. To this extent, we use a multinomial logit model estimated on data corresponding to the results of the inspections in the year 2015 in Italy. The model controls for two fixed effects represented by the type of operator and a contextual variable, i.e., the region where a firm is located. Significant variability in CBs behavior could induce adverse selection in the choice of the CB by organic operators. In this vein, we discuss some implications in terms of policies and consequences for supervision in the conclusions.
Keywords: 330; Organic certification; Risk analysis; Logit models; Italy